Improvement of Mathematical Problem Solving Ability Through Problem Based Learning Model In Applied Mathematics Course II In Industrial Engineering Program of Polytechnic of South Aceh - Resky Rusnanda; Safwandi Safwandi (LPPM Politeknik Aceh Selatan, 2018)
This research is a quantitative research by true experimental design. Research design is random, pre test and post test. Sample is prepared randomly by two group; experiment and control group. Experiment group is prepared by problem based learning with 13 students in this group, while control group is taught by conventional method with 10 students in this group. Tests are applied in data collecting, then analyzed by t-test. Data analysis shows at α = 0,05 there was 1,72. It can be concluded that the increase in mathematical problem solving from experiment group is relatively better than those in control group in Applied mathematics II Course in Industry Technics Study Program, South Aceh Polytechnic.